Developing an integrated disaster risk reduction strategy to enhance the resilience of vulnerable communities - Fumiso Muyambo; Johanes Belle; Yong Sebastian Nyam; Israel R. Orimoloye (Sustainable Environment)
QwaQwa in the Free State province of South Africa is exposed to high disaster risk driven by high exposure to multiple climate change-related events, such as droughts, flooding, wildfires, water scarcity. This paper analysed and developed sustainable disaster risk reduction and resilience strategies to mitigate multiple climate-related hazards in QwaQwa. Using a participatory approach, data were collected from a household survey of 340 participants and 9 key informant interviewees. The main findings indicate that communities with strong community capitals and active participation in disaster risk reduction initiatives are better equipped to identify risks and implement effective interventions. The results were used to propose strategies including; inter alia, developing a disaster risk reduction plan for the municipality, applying nature-based solutions, maintaining and developing more climate-resilient infrastructure, improving community participation in disaster risk reduction issues, building partnerships with other municipalities and the private sector and proper public resource management. This set of strategies will contribute to building resilience to multiple climate change hazards in QwaQwa and other areas in the world facing similar conditions.